P171 Subfertility in young patients with Crohn′s disease. A case-control study. (30th January 2023) - Gutiérrez Casbas, A; Bernal, L; Zapater, P; Herreros, B; Rodríguez, A; Muñoz, R; Madero, L; Orts, B; Belen, O; Sempere, L; Torregrosa, M E; Moreno-Pérez, O; et al.
Abstract: Background: Inflammatory bowel disease (IBD) commonly affects women and men during the reproductive years.The effect of the disease burden on fertility in these patients is a common concern for them. ECCO guidelines establish that active disease is associated with decreased fertility in women but studies regarding this topic are of low quality and outdated. Aims: to investigate the effect of CD on fertility, studying ovarian reserve in women as well as global Sertoli cell function in men, - To compare these results of CD patients with the healthy control group. (HC) - To assess the related factors to subfertility in women and males with CD. Methods: This was a cross-sectional, prospective and case-control study, including CD patients, aged 18-40 years-old, and HC matched by gender and age (ratio 2:1). Morning baseline IB was measured in men using ELISA. Serum anti-Müllerian hormone (AMH) was measured by ECLIA. Sociodemographic and phenotypic features of CD patients and controls were collected.Subfertility was defined as IB < 89pg/mL, AMH <1.66 ug/L in 0-24 years old group; <1.18 ug/L in 25-29 years old group; <0.67 ug/L in 30-34 years old group; <0.77 ug/L in 35-39 years old group; and <0.01 ug/L in 40-44 years old group. AMH <2 ug/L in women under 40 was considered low. Results: A total of 163 individuals were included: 83 men (58 CD, median 28 years old, RIQ 24-36; 25 HC, median 31 years old, RIQ 26-37) and 80 women (50 CD, median 26 years old, RIQ 21-36; 30 HC, median 28, RIQ 26-32). Sedentary lifestyle was more frequent in women with CD vs HC (46% vs 3, 3%, p<0, 001). 24% of women with CD and 8% of males had clinical activity (IHB >4). Low AMH (<2ug/L) in women older than 30 was more frequent in CD vs HC: 95% (18/19) vs 44% (4/9) p =0.001, with an OR of presenting AMH < 2 ug/L of 3.28 (IC 95%, 1.6-6.4) for women with CD >30 years old. The average AMH serum level was similar between women with CD and HC [1.83 (1.04-3.34) vs. 2.74 (1.05-4.12) g/L, p =0.4]. Abnormal AMH rate by age rank was not different between groups in global population (11/50, 22% EC vs. 7/30, 23% in CS, p =0.9, ). IB levels were significantly lower in men with CD vs HC [169 (140-217) vs 232 ug/L (178-274) p=0.001]. IB <89 pg/mL was not detected in any control vs 6% (n=3) in CD. In multivariate analysis, only AMH was associated with lower levels of IB in CD men, no association with clinical activity or treatments in CD was found. Conclusion: Women with CD and >30 years old have a higher risk than general population of presenting low AMH (<2).These data could be helpful at council of women with CD that desire to have progeny. IB concentration was lower in men with CD compared to HC.